2017
DOI: 10.1021/acschemneuro.7b00385
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Positron Emission Tomography Radiotracer for Imaging Elevated Levels of Superoxide in Neuroinflammation

Abstract: Reactive oxygen species (ROS) are believed to play a major role in the proinflammatory, M1-polarized form of neuroinflammation. However, it has been difficult to assess the role of ROS and their role in neuroinflammation in animal models of disease because of the absence of probes capable of measuring their presence with the functional imaging technique positron emission tomography (PET). This study describes the synthesis and in vivo evaluation of [18F]ROStrace, a radiotracer for imaging superoxide in vivo wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 26 publications
2
99
0
Order By: Relevance
“…"Wet" biopsies are spatially non-specific and tissue biopsies are generally unavailable. Imaging brain oxidative stress and the effects of treatment in vivo has so far required the use of exogenous redox probes that are not FDA approved, limiting such studies to animal models (Bačić et al 2015;Hall et al 2012;Hou et al 2018). The goal of this study is to begin to address the long-standing unmet need to measure oxidative stress in vivo with high spatial resolution using an endogenous biomarker to confirm localized efficacy of anti-oxidant treatment in hippocampus CA1 in both experimental models and, ultimately, in patients.…”
Section: Introductionmentioning
confidence: 99%
“…"Wet" biopsies are spatially non-specific and tissue biopsies are generally unavailable. Imaging brain oxidative stress and the effects of treatment in vivo has so far required the use of exogenous redox probes that are not FDA approved, limiting such studies to animal models (Bačić et al 2015;Hall et al 2012;Hou et al 2018). The goal of this study is to begin to address the long-standing unmet need to measure oxidative stress in vivo with high spatial resolution using an endogenous biomarker to confirm localized efficacy of anti-oxidant treatment in hippocampus CA1 in both experimental models and, ultimately, in patients.…”
Section: Introductionmentioning
confidence: 99%
“…Besides 62 Cu-/ 64 Cu-ATSM, several PET radioligands for imaging of the redox status have been developed, such as 18 F-FASu for the cystine/glutamate transporter [171], 18 F-ROStrace for superoxide [172], and 18 F-FDHM for ROS [173]. These new radioligands are promising but are still in the preclinical stage with animals.…”
Section: Development Of Imaging Techniques For Oxidative Stressmentioning
confidence: 99%
“…In a follow-up study to their earlier work with [ 18 F]FDMT, Mach and coworkers reported the synthesis, in vitro characterization, and in vivo evaluation of [ 18 F]ROStrace in an LPS-induced mouse model of neuroinflammation [ 60 ]. In this study, the investigators reported that replacing the corresponding triazole “click” moiety with the traditional [ 18 F]2-fluoroethoxy group resulted in a compound that freely crossed the BBB.…”
Section: Pet Radiotracers For Imaging Rosmentioning
confidence: 99%
“…A key observation in this study was the high variability in uptake of [ 18 F]ROStrace in the LPS-treated animals. However, when the investigators compared the uptake of [ 18 F]ROStrace with the degree of “sickness” following the LPS-treatment by using the scoring criteria outlined by Carstens and Moberg [ 61 ] for recognizing pain and distress in laboratory animals, there was a high correlation between radiotracer uptake and degree of sickness induced by LPS ( Figure 6 ) [ 60 ]. The authors also conducted a detailed metabolite analysis study, confirming that the radioactive species in the LPS-treated animals was primarily the oxidized form of [ 18 F]ROStrace, [ 18 F] ox -ROStrace.…”
Section: Pet Radiotracers For Imaging Rosmentioning
confidence: 99%